Analysis of Factors Affecting Student Learning Achievement of Social Sciences Subjects in Muhammadiyah Middle School Rokan Hulu Regency - Reni Efriza; Caska Caska; Makhdalena Makhdalena (Journal of Educational Sciences, 2020)
The Social Sciences subject examination score in Muhammadiyah Rambah Middle School is still below the average. This phenomenon is inseparable from the low student achievement. This study aims to analyze the factors that influence student learning achievement. This type of research was quantitative research. The population in this study was VII grade students of SMP Muhammadiyah Rambah which was conducted in the even semester of the 2018/2019 school year. The sample was carried out using proportional random sampling technique with 76 respondents. Data collection using a questionnaire with a Likert scale and then the data were analyzed by path analysis. The results of the analysis show that learning discipline has an indirect effect on learning achievement through learning motivation of 0.0897, with a total influence is 0.351 with an effective contribution of 12.29%. The family environment has an indirect effect on learning achievement through learning motivation of 0.1054, with a total influence of 0.354 with an effective contribution of 12.56%. This shows that learning achievement can be improved if the quality of learning discipline, family environment and student motivation are improved.